(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
In the context of a competency-based approach to learning, it is important to combine the acquisition of subject knowledge with the development of socially significant skills and abilities. In this context, game teaching aids are an effective tool for activating cognitive activity and forming communicative and social competencies of students. The article examines the essence and content of the concepts of «communicative competence» and «social competence», determines their interrelationships and role in modern education. The main types of game tools that are appropriate for use in biology lessons are described, in particular role-playing, business, simulation and digital games, educational quests and exercises with elements of research. The didactic potential of game tools is revealed, which consists in creating situations of active interaction, development of speech skills, critical thinking and responsibility for a common result. Particular attention is paid to the pedagogical conditions for the effective use of game technologies: determining the didactic goal, matching the forms of game activity to the age and individual characteristics of students, creating a favorable psychological climate, organizing various forms of interaction and pedagogical support. Practical possibilities for integrating game technologies into the content of biological education are outlined, which ensure a combination of mastering the educational material with the development of social and communicative competencies. The results of the analysis confirm that the systematic and methodically justified use of game tools in the process of teaching biology contributes to the formation of complex competencies in students, increases motivation for learning and stimulates active interaction in the team.